IMPLEMENTASI PROGRAM PPA-PKH DI KABUPATEN PROBOLINGGO 2013 (PENARIKAN PEKERJA ANAK KE SEKOLAH FORMAL/INFORMAL) - Rahmadi, Andhi Nur (Program Studi Ilmu Pemeritahan Fakultas Ilmu sosial dan Ilmu Politik Universitas 17 Agustu, 2017)
Abstraction This paper description about withdrawal of childs labor to school or training center. One of the important stages in the cycle of public policy is policy implementation. Implementation is often considered just an implementation of what has been decided by decision makers, as if the stage is less influential. But in reality, the implementation stage is so important because a policy will not mean anything if it can not be implemented properly. Exploitation of child labor is not just about wages, but about long working hours, the risk of accidents, health problems, and become the object of harassment and abuse adults. In some studies, the majority of child laborers work more than 7 hours per day. Though based on Law Number 13 Year 2003 concerning Manpower, age less than 12 years should not be working, 13-14 years of age may only work 3 hours/day, and 15-17 years of age may work 8 hours/day but in a condition that does not endanger physically and mentally. Reality on the ground, most of the working children aged 13-14 years who work an average of 6-7 hours/day. In fact, many children are working in hazardous sectors and inhuman to be done by the children. Indeed, the government has made ​​several attempts to save the poor children through the PPA program - PKH. But this is not enough because the main problem is structural poverty. That is, as long as the wheel rotates, the structural poverty child labor will continue to mushroom. Scholarships for poor children just like putting out fires. Therefore, in addition to providing assistance subsidy, the government should seriously empower the poor by implementing the principles of social economy. Keywords: Implementation, child labor, poverty, PPA-PKH